Humoral immune activation within tertiary lymphoid structures is correlated with poor outcomes in oral lichen planus and lichenoid lesions - Yang, Xiaojie; Dai, Annan; Lai, Yirao; Pan, Lei; Deng, Yiwen; Shen, Xuemin; Han, Xiaozhe; Sun, Lei; Wang, Yufeng; Tang, Guoyao (Frontiers in Immunology, 2025)
BackgroundOral lichen planus (OLP) and oral lichenoid lesions (OLL) are chronic immune-mediated mucosal disorders with heterogeneous clinical presentations. While T cell-mediated mechanisms have been extensively studied, the role of humoral immunity, particularly B cell activation and plasma cell differentiation, remains insufficiently understood.MethodsRNA sequencing datasets from healthy oral mucosa and OLP lesions were integrated and analyzed to identify differentially expressed genes. Consensus clustering based on a validated tertiary lymphoid structure (TLS) signature genes (TSGs) was used to define immune subtypes. Associations with clinical severity and recurrence were validated in an independent RNA-seq cohort. Immunohistochemistry analysis of CD20+ B cells and CD38+ plasma cells was conducted in a separate clinical cohort of OLP/OLL patients.ResultsBased on TSGs, two immune subtypes were identified: Subtype A was enriched for CCL3, IL2RA, and IL1R2. Subtype B exhibited elevated expression of humoral activation markers IRF4 and TNFRSF17 and enrichment of B cell-related pathways. Transcriptomic features of Subtype B were significantly associated with erosive and recurrent OLP cases. Immunohistochemistry confirmed that CD20+ B cells were enriched in TLS-like structures (P < 0.001), whereas CD38+ plasma cells were closely linked to erosive phenotypes (P = 0.038).ConclusionsTLS-associated B cell maturation and plasma cell infiltration define a humoral activation axis linked to unfavorable clinical outcomes in OLP/OLL. The presence of activated B cells and plasma cells correlates with erosive and recurrent disease phenotypes, highlighting their potential as prognostic biomarkers and therapeutic targets for improving disease management.